STRATEGIC VECTORS OF THE DEVELOPMENT OF HEALTH CARE INSTITUTIONS IN THE CONDITIONS OF WAR AND POST-WAR RECONSTRUCTION - NYTKA, Оlena (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Identification of the challenges and threats faced by Ukrainian healthcare institutions in wartime conditions and the identification of strategic development vectors that are important and effective both during the war and in post-war reconstruction.The article uses the following research methods: the systemic analysis method – for collecting, analyzing, and comparing contemporary scientific research on the strategic development of healthcare institutions; the statistical analysis method – for comparing the number of destroyed and damaged healthcare facilities with the number of civilian casualties and injuries resulting from the full-scale Russian invasion; the methods of induction and deduction – for identifying contemporary challenges for healthcare institutions caused by the war.The analysis of the challenges and threats faced by Ukrainian healthcare institutions highlighted the most significant among them: the increase in the number of destroyed and damaged healthcare facilities and the number of injured and killed medical staff; the increase in civilian casualties and injuries, etc. Based on these identified challenges, strategic development vectors for Ukrainian healthcare institutions during the war and post-war recovery are proposed: ensuring basic safety for patients, medical staff, and citizens; enhancing international cooperation; developing the system of rehabilitation medical services; advancing telemedicine, etc.The scientific novelty of the conducted research lies in defining contemporary challenges and threats to the activities of Ukrainian healthcare institutions and identifying strategic development vectors for these institutions in wartime conditions and post-war reconstruction.The research results have formulated strategic development vectors for healthcare institutions in wartime and post-war recovery, which can be considered by current healthcare institutions when developing their strategic plans.
Keywords: strategic management; strategic development; healthcare institutions; healthcare system; civil safety; rehabilitation services